Applying behaviour change theory to parent‐led language interventions for children in the early years - Barnett, Sarah E.; Stringer, Helen; Letts, Carolyn (International journal of language & communication disorders, 2024)
Background The aim of many interventions used by speech and language therapists (SLTs) is to change behaviours related to communication and interaction. Parent‐led language interventions for children in the early years (0–5 years) rely on SLTs supporting parents to change their behaviour in child‐focused interactions to effect a change in the child's communication. Therapeutic techniques used by SLTs in parent‐led language interventions are largely underspecified, impacting on intervention reporting, replication, trialling and development. The Behaviour Change Technique Taxonomy Version 1 (BCTTv1) offers a method of describing intervention techniques developed for use in public health interventions, but with several examples of its application to speech and language interventions. Aims To identify behaviour change techniques (BCTs) from the BCTTv1 occurring in parent‐led language interventions for children in the early years. Methods & Procedures A literature search identified relevant descriptions of parent‐led language interventions. These were coded using the BCTTv1. A reliability check was carried out on 10% of the descriptions. To confirm the use of identified BCTs in clinical practice, results of the literature search were triangulated with an online survey of SLTs, and observations of SLTs delivering parent‐led language intervention. Outcomes & Results A total of 84 papers containing descriptions of 45 interventions were coded; 62 SLTs responded to the survey and three SLTs were observed delivering parent‐led language intervention. A total of 24 BCTs were identified in the literature search, replicated in the observations and verified by SLTs in the survey. BCTs were identified at two levels: Level 1 SLT implemented to change parent interactive behaviour; and Level 2 parent implemented to change child communicative behaviour. Conclusions & Implications The BCTTv1 is a useful starting place for describing parent‐led language interventions. With some additions and adjustments, BCTs identified in this study were immediately recognized by practitioners and can easily be adopted into practice. WHAT THIS PAPER ADDS What is already known on this subject Techniques used in SLT interventions are often not clearly described. The BCTTv1 has been used to clarify technique descriptions with success in a small number of SLT disciplines, but not yet in parent‐led language interventions for preschoola children. What this paper adds to the existing knowledge This paper constitutes the first research into quantifying the techniques used in parent‐led language interventions using the BCTTv1. What are the potential or actual clinical implications of this work? This paper provides a clear list of techniques used by SLTs implementing interventions for preschool children, which can be immediately adopted and used in practice. It also highlights potential adjustments and gaps in the BCTTv1 in relation to SLT which can contribute to future iterations.